Assessments of Mutagenic and Genotoxic Effects of Noodles using Salmonella Typhimurium and Caenorhabditis Elegans as a Model Organism - Usman Usman Musa; Edith Adanna Onwuliri (UMYU Journal of Microbiology Research, 2025)
Study’s Excerpt: